The Relationship Between Parent-Child Communication and Student Self-Confidence at RA Ma'arif 1 Metro - Fitria Hani Aprina; Yuning Eka Rahma Wati; Riyan Jaya Sumantri (Journal of Childhood Development, 2023)
The purpose of this study is to determine whether there is a relationship between parent-child communication and self-confidence in RA Ma'arif 1 Metro students. This research is a descriptive quantitative correlational research. With a population of female students of RA Ma'arif 1 Metro and a population of 60 people. Sampling in a purposive way. The research sample amounted to 35 people, the sample was taken based on the characteristics or properties of the population that were known beforehand. Data collection was carried out using a scale, namely the parent and child communication scale and the self-confidence scale. The data analysis technique used is product moment correlation analysis (r) of 0.482 with p < 0.05. The results of the study obtained communication that occurs between parents and children in the high category, as much as 55% in the high category, 45% in the medium category and 5% in the low category. While self-confidence is obtained 60% in the medium category, 35% in the high category and 5% in the low category. Suggestion: Parents can anticipate this by further improving communication between parents and children. Schools understand the importance of collaborating with parents to anticipate the emergence of forms of misparenting behavior, especially those caused by a lack of communication between parents and children.